Methods of Analysis of Metal Ions - Attimukat; Anshul Bansal (Innovations in Science and Technology: Shaping a Sustainable Future (Vol. 2), 2024)
The different metal ions are present in drinking water and other daily life products like cosmetics, fruits and vegetables, food packaging papers, medicines, etc. These metals may enter human bodies through food and water by bioaccumulation. The concentration of these metals beyond their tolerance limits may prove harmful to human beings. So, it is necessary to develop accurate and cost-effective methods for the analysis of these metal ions. There are various techniques and various methods for the determination of different methods. AAS and UV-visible spectrophotometer techniques are cost-effective and involve selective and sensitive methods for determination. A few of the latest methods for the determination of different metal ions are summarized here.